Un recurso para atención primaria de la salud mental. DASS-21, propiedades psicométricas - Marco O. Vargas-Olano; Sandra P. Cárdenas-Ojeda; Carolina Herrera -Delgado (Universidad Nacional Hermilio Valdizán, 2022)
Objective. Determine the psychometric characteristics of DASS-21 and identify its advantages as an aid in the diagnosis and screening of mental health disorders (depression, anxiety and stress). Materials and methods. Descriptive and cross-sectional study. The sample was non-probabilistic of 964 university students from different regions of Colombia who met the selection criteria and answered the questionnaire. Using Cronbach's Alfa, the internal consistency of the questionnaire was measured and exploratory factor analysis was applied for the validation of the construct, using a methodology of main axes with varimax factor rotation. To establish the number of factors to be conserved, the Kaiser criterion was used. It was considered significant with p value <0.05. Results. The questionnaire was answered by 964 students. Reliability characteristics were corroborated (Cronbach's Alpha obtained for the total of 21 items a value of 0.93) and in the subscales obtained values higher than 0.8 (depression 0.85, anxiety 0.82 and stress 0.85). To determine the suitability of carrying out the factor analysis, the Bartlett sphericity test was performed, which yielded a p < value 0.0001, was later calculated the measure of adequacy of the Kaiser sample, called Kaiser-Meyer-Olkin (KMO), whose value was 0.95, expressing that it is appropriate to perform the factor analysis. Conclusions. Its use at the primary level of health care is recommended, both to support the diagnosis and as a follow-up criterion in patients with depression, anxiety and stress.